NEED ANALYSIS IN DEVELOPING RME-BASED DIGITAL TEACHING MATERIALS OF MATHEMATICS FOR JUNIOR HIGH SCHOOL - Pitriani, Pitriani (Universitas Muhammadiyah Makassar, 2024)
Needs analysis is the initial study in development research. This analysis is necessary to produce the right product. This study tries to find out whether digital teaching materials based on the RME approach on curved-face three-dimensional shapes materials need to be developed. The method used is descriptive research. Data were collected using a questionnaire. Technical analysis of data is done by processing and analyzing data using a Likert scale. The respondents in this study are 32 students and 5 mathematics teachers of a junior high school in Palembang. The data were collected using a questionnaire, observation, and interview. The data were analyzed descriptively. Based on the need analysis, it can be concluded that it is necessary to develop RME-based digital teaching materials. Digitalization is needed in learning in this era.